Alat Peringatan Pelanggaran Physical Distancing Berbasis Raspberry Pi sebagai Upaya Preventif Penyebaran Covid-19 pada Era New Normal - Hilal Fahrul Hamam; Irwan Ardiansyah; Burhan Dwi Ardiandyah; Dira Tri Puspita; Nancy Febriani Taek; Ardy Seto Priambodo (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2021)
The Covid-19 pandemic that hit Indonesia forced the Indonesian population to be ready with a new normal order. With this condition, it is hoped that the community can implement changes to the new order of life by implementing health protocols. But nowadays, people often violate health protocols, physical distancing, which is one form of prevention in the new normal era. The innovation of a Raspberry Pi-based tool designed to produce warnings for physical distancing violations is expected to minimize violations. The camera installed on the system will help detect the distance between two or more people and will give a warning to immediately carry out physical distancing if the measured distance is less than 1 meter. The purpose of writing this research is to design a system and concept of